Agritourism as a Model for Subak Conservation in Bali - Surya Diarta, I Ketut; Sukendar, Ni Made Classia; Sudana, I Putu (Department of Forest Resources Conservation and Ecotourism - IPB University, 2026)
This research investigates the role of agritourism in conserving Subak Jatiluwih as a UNESCO World Heritage Site in Bali, based on the Tri Hita Karana philosophy. This study seeks to investigate how agritourism operates as a device for the conservation of traditional agricultural landscapes when threatened by modernisation and tourism.The study employed an ethnographic case study involving fieldwork, interviews, participant observation, and document analysis. Fieldwork was conducted from June to November 2024, using purposive sampling to gather insights from 20 informants, including Subak leaders, farmers, tourism actors, community representatives, government officials, and visitors, providing a comprehensive, multilevel understanding of Subak Jatiluwih. This study identified four critical means by which agritourism promotes conservation: institutional strengthening, ritual conservation, experiential engagement, and the equitable distribution of benefits. Agritourism ensures the continuity of traditional farming and contributes to the dissemination of spiritual-ecological values and the involvement of the youth and the population of the communities concerned. However, there have also been criticisms of issues ranging from unequal benefits to cultural commodification. This evidence-based study demonstrates that adaptive and inclusive governance are essential for achieving fair outcomes. The framework provides transferable lessons on how agritourism can mediate economic, ecological, and cultural interests in heritage landscapes and offers a template for other rural contexts in Southeast Asia and elsewhere.